2010
DOI: 10.1016/j.cogpsych.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A modular geometric mechanism for reorientation in children

Abstract: Although disoriented young children reorient themselves in relation to the shape of the surrounding surface layout, cognitive accounts of this ability vary. The present paper tests three theories of reorientation: a snapshot theory based on visual image-matching computations, an adaptive combination theory proposing that diverse environmental cues to orientation are weighted according to their experienced reliability, and a modular theory centering on encapsulated computations of the shape of the extended surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 60 publications
5
88
2
2
Order By: Relevance
“…Current investigators who seek to maintain a modular model to cover the range of findings on navigation by animals and young humans generally add ancillary processes or make new distinctions. Spelke and her collaborators (e.g., Lee & Spelke, 2010a;Spelke, Lee, & Izard, 2010) have presented a reconceptualization.…”
Section: Modularity Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Current investigators who seek to maintain a modular model to cover the range of findings on navigation by animals and young humans generally add ancillary processes or make new distinctions. Spelke and her collaborators (e.g., Lee & Spelke, 2010a;Spelke, Lee, & Izard, 2010) have presented a reconceptualization.…”
Section: Modularity Theorymentioning
confidence: 99%
“…Because the original proposal made by Cheng (1986) is untenable in its strictest form (Cheng, 2008;, we focus on considering a revised modular proposal that has been recently put forward (Lee & Spelke, 2010a. In this context, we discuss issues concerning the basic distinction between geometry and features.…”
Section: Introductionmentioning
confidence: 99%
“…If the chicks reorient exclusively on the basis of a mental representation of the geometric cues provided by the macroscopic three-dimensional surface layout [10][11][12]26], a generalization decrement should be expected specifically in the LO geometry condition, in which the geometric contribution provided by the walls of the arena were no longer available. An alternative hypothesis has been tested that chicks rely on a mental representation of the environmental axis to reorient and therefore on the basis of both the spatial distribution of extended surfaces and discrete objects in the scene [42].…”
Section: (B) Experimental Set-upmentioning
confidence: 99%
“…Although vertebrate species reorient efficiently according to geometric cues provided by the shape of an arena, both humans [7][8][9][10][11][12] (but see [13]) and non-human animals [14][15][16] usually fail to reorient according to geometric cues provided by freestanding objects in an array of a similar geometric shape. It has been hypothesized that the macroscopic, three-dimensional surface layout of an environment geometry may have a primacy for visuo-spatial reorientation over other sources of geometric cues, including those provided by discrete objects in arrays, because the former cues are distinctive, stable and enduring over time in a natural environment [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that children's reorientation is based on the computation of distances, but not lengths, between extended three-dimensional surface layouts. Moreover, disoriented children also fail to encode angle relationships between surfaces, and they encode distance relationships between wall-like surfaces but not between freestanding objects or fragmented corners (Gouteux and Spelke, 2001;Lee and Spelke, 2008;Lee and Spelke, 2010;Lee and Spelke, 2011;Lee et al, 2012a). Importantly, children use these geometric properties not only to solve the navigation problems faced by other animals, but also to solve the uniquely human problem of navigating by a map (Huang and Spelke, 2013).…”
Section: Introductionmentioning
confidence: 99%